Quality of Life in the Greater Santa Fe area: changes, continuities and analytical dimensions (2001 and 2010) (Huellas, 2015)
The purpose of this study is to scrutinize the quantitative and spatial changes related to transformations of urban quality of life in the Santa Fe Urban Agglomeration (Argentina), between the years 2001 and 2010. This study provides objective indices of quality of life, which are sustained by a multidimensional view of the material conditions of life in urban populations. In this sense, indicators related to education, health policy impact, infrastructure and environmental shock are adopted for each of the 493 census tracts of the Santa Fe Urban Agglomeration. These indicators are organized in two dimensions, 'private' and 'public', in order to show two different facets of quality of life. Data sources are the National Census of Population, Households and Housing corresponding to the years 2001 and 2010, carried out by the Statistics and Census National Institute (INDEC), and the National Water Institute (INA). Measurement and evolution of the quality of life index and of the 'dimensions' illustrate the reasons for the change process and identify at least four spatial patterns of the trend within the period under consideration. The results allow recognizing the differential impact of the two 'dimensions' considered, among the various sectors of the agglomeration. And, in turn, they allow for the construction of new knowledge related to a characteristic pattern, and to the recent changes in the spatial distribution in life conditions of the population in the Santa Fe Urban Agglomeration.
Keywords: Quality of life; index; changes; urban structure